Bond strength and interfacial morphology of different dentin adhesives in primary teeth. - Pallavi Vashisth; Mudit Mittal; Mousumi Goswami; Seema Chaudhary; Swati Dwivedi (Tehran University of Medical Sciences, 2014)
To evaluate the interfacial morphology and the bond strength produced by the three-step, two-step and single-step bonding systems in primary teeth.Occlusal surfaces of 72 extracted human deciduous teeth were ground to expose the dentin. The teeth were divided into four groups: (a) Scotchbond Multipurpose (3M, ESPE), (b) Adh Se (Vivadent), (d) OptiBond All-in-One (Kerr) and (e)Futurabond NR (VOCO, Cuxhaven, Germany). The adhesives were applied to each group following the manufacturer's instructions. Then, teeth from each group were divided into two groups: (A) For viewing interfacial morphology (32 teeth), with 8 teeth in each group, and (B) For measurement of bond strength (40 teeth), with 10 teeth in each group. All the samples were prepared for viewing under SEM. The statistical analysis was done using SPSS version 15.0 software.Observational measurement of tag length in different adhesives revealed that Scotchbond had the most widely spread values with a range from 12.20 to 89.10μm while OptiBond AIO had the narrowest range (0 to 22.50). The bond strength of Scotchbond Multipurpose was significantly higher (7.4744±1.88763) (p